Biliteracy and reading ability in children who learn Greek as a second language. Issue 8 (13th September 2020) - Rothou, Kyriakoula M.; Tsimpli, Ianthi
ABSTRACT: The differences and similarities in the word recognition and reading comprehension skills of monoliterate Albanian-Greek (ML2), biliterate Albanian-Greek (BL2) and monolingual (L1) children in grades 3–6 were examined in two cross-sectional studies. Participants completed standardized and experimental tasks measuring cognitive, oral language and reading skills. The first study explored the effect of biliteracy on Greek word recognition taking into account the impact of oral expressive vocabulary in that language. 24 BL2 and 66 ML2 were compared to 78 L1 speakers in visual word recognition. It was revealed that the two groups of bilingual children differed in word recognition. In addition, it demonstrated that oral proficiency in the second language can play a key role in second language word reading. Study 2 examined the differences in reading comprehension skills of 21ML2, 13BL2 and 19L1 children. ML2 children performed proficiently on text comprehension as their monolingual peers. However biliterate Albanian-Greek children had poorer performance than their L1 peers.